PENGARUH PEMAHAMAN FIKIH IBADAH SALAT TERHADAP KEDISIPLINAN SALAT FARDHU PESERTA DIDIK DI MADRASAH ALIYAH RAHMATUL ASRI KABUPATEN ENREKANG - Hasyim Anwar, Farid; Hafid, Erwin; Rusmin B, Muhammad; Syahruddin; Achruh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims effect the level of students’ understanding of the jurisprudence of prayer, describe the discipline of performing obligatory prayers, and analyze the influence of understanding the jurisprudence of prayer on the discipline of obligatory prayer among students at Madrasah Aliyah Rahmatul Asri, Enrekang Regency. This research employed a quantitative approach using an ex post facto method with a simple linear regression design. The population consisted of 106 students, while the sample comprised 53 students selected using random sampling. Data were collected through questionnaires and analyzed using descriptive and inferential statistical techniques. The descriptive analysis showed that students’ understanding of the jurisprudence of prayer was in the moderate category, with a percentage of 66.03%, while the discipline of performing obligatory prayers was also in the moderate category, with a percentage of 71.69%. The results of hypothesis testing showed that the calculated t-value was 2.285, while the t-table value was 1.674 at a significance level of 0.05. Since the calculated t-value was greater than the t-table value, H0 was rejected and H1 was accepted. Therefore, there is a significant influence of students’ understanding of the jurisprudence of prayer on their discipline in performing obligatory prayers at Madrasah Aliyah Rahmatul Asri, Enrekang Regency.